Exploring the Transformational Role of Regular Nature-Based Adventure Activity Engagement in Mental Health and Long-Term Eudaimonic Well-Being - Gill Pomfret; Manuel Sand; Carola May; Jelena Farkić (Behavioral Sciences)
This article investigates the transformative impacts of regular nature-based adventure activity engagement and its long-lasting effects on eudaimonic well-being (EWB), specifically mental health. Although extant research highlights a wide range of well-being and mental health benefits from participation in such pursuits, less is known about experienced outdoor adventure enthusiasts for whom adventure is a fundamental and transformational part of their lives. The study builds on an existing conceptual framework that synthesizes pertinent research concepts on nature-based activity engagement and subjective well-being benefits. It presents key findings from 40 semi-structured in-depth online interviews with respondents from the UK, Germany, and Serbia. Interview data were collated and analyzed using a thematic framework approach. The findings highlight the importance of outdoor adventure activity engagement for respondents’ mental and physical health and long-term well-being. Regular activity participation can be transformational in reducing feelings of ill-being and enhancing EWB. It can improve self-efficacy and identity development and promote the fulfilment of psychological needs, facilitated by key transformational catalyzers. Continually entering a liminal state, experiencing emotions, and overcoming challenges and risks during engagement are crucial to “successful” long-lasting transformation. Further research should continue to explore adventure’s transformational and EWB benefits to develop long-term data.